Disturbed integrin expression in the vascular media in CADASIL - Dziewulska, Dorota; Nycz, Ewelina (Folia Neuropathologica, 2016)
CADASIL (cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy) is an inherited angiopathy characterized by degeneration and loss of vascular smooth muscle cells (VSMCs) of still unknown pathomechanism. Many functions of VSMCs, such as adhesion, apoptosis, contraction, differentiation, migration, and proliferation are determined by integrins – surface adhesion receptors involved in binding and interactions between cells and extracellular matrix (ECM). Since integrins play such an important role in VSMCs biology, disturbances in their expression may influence myocytes behavior and fate in CADASIL. In this study, we focused on the most important compounds of VSMCs integrins: subunits α 4 , β1, and β 3 in an attempt to elucidate their immune expression in the arterial media of CADASIL patients. The immunohistochemistry revealed a decreased expression of integrin β1 subunit (p < 0.001) but similar to the control expression of integrin subunits α 4 and β 3 . Decreased β1 immunoreactivity was observed in capillary vessels, arterioles, and small arteries. The abnormal immune expression of integrin β1 subunit was found even in microvessels without microscopically noted degenerative changes, which suggests that this is an early phenomenon in CADASIL. Since integrin β1 subunit is a compound of 10 heterodimer integrin receptors, its disturbed expression may significantly influence VSMCs biology leading to myocytes degeneration and loss via anoikis – a type of apoptotic cell death due to loss or inappropriate cell adhesion to ECM.